On the Threshold of Delinquency - Mays, John Barron (Liverpool University Press, 1959)
In this 1959 study, John Barron Mays presents the results of a novel piece of social research through which he seeks to demonstrate that a better start in life can be given to children being brought up in a substandard social environment by mobilising voluntary and public social services. The focus is the development of a new kind of boys' club. A preface is provided by T. S. Simey of The University of Liverpool.